Outline of a child rights-based approach in early childhood education & care services - Premoli, Silvio (Revista Eletrônica de Educação, 2024)
According to the new directions in Child and Family Welfare services (Premoli, 2012), ECEC services in Europe are also increasingly characterized by new emerging orientations, perspectives, and approaches, which recur in different national contexts, driven by the influence of the United Nations Convention on the Rights of the Child (CRC) and of the policies to support integration promoted first by the European Community and then by the European Union. In particular, reference is made to: the affirmation of an educational and pedagogical attention to the child as a whole (the whole child); the emergence of anti-deterministic paradigms such as resilience, the increase of strengths, and the pursuit of beauty; listening to the children’s point of view and promoting their participation; the intercultural approach; the growing attention to evaluation in order to improve quality and effectiveness; finding solutions to the contrast between the rights of the child and the rights of adults (parents or educators); the involvement of families; the openness towards local communities and territories; the consultation with the other services (wrap-around services) and the composition of professional and disciplinary views; the development of strategies that favour continuity between the various school levels. In Herczog’s perspective (2012a), the adoption of an approach based on child rights is a strategy which, among other things, allows for an immediate return on investments in the field of ECEC. It therefore seems necessary to define the Child Rights-Based Approach as an essential professional skill for professionals working in ECEC services.